The effect of lithium tetraborate as a novel cardioprotective agent after renal ischemia-reperfusion injury - Kubra Koc; Fatime Geyikoglu; Asli Yilmaz; Serkan Yildirim; Gulsah Yildiz Deniz (Universidade de São Paulo, 2023)
Abstract Epidemiological studies suggest that acute kidney injury has certain effect on myocardial function. In this study, for the first time, we tested a boron compound namely lithium tetraborate an act as an anti-oxidant and anti-inflammatory agent in ischemia-reperfusion injury. For this, we employed an in vivo rat model with kidney ischemia reperfusion injury to evaluate cardiac injury to clarify the mechanisms of lithium tetraborate. The evaluation of cardiac injury through kidney artery occlusion and reperfusion rat model indicated that lithium tetraborate could (1) reduce oxidative stress-induced endothelial dysfunction; (2) attenuate the inflammatory response of cardiac cells; and (3) alleviate the apoptosis and necrosis of myocytes. In summary, lithium tetraborate demonstrates significant therapeutic properties that contribute to the amelioration of cardiac damage, and it could be a promising candidate for future applications in myocardial dysfunction.